2016
DOI: 10.1089/lap.2016.0032
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Splenectomy and Esophagogastric Devascularization for Liver Cirrhosis and Portal Hypertension Is a Safe, Effective, and Minimally Invasive Operation

Abstract: This meta-analysis demonstrated that laparoscopic left lateral resection is a safe and feasible option associated with a reduced overall complication rate. The current evidence suggested that it could be performed routinely in liver centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 17 publications
1
11
0
1
Order By: Relevance
“…Although splenectomy is performed for patients with hypersplenism in some institutions[21,42], hypersplenism in most patients should be considered a laboratory abnormality that does not require treatment or further consideration[43]. However, a previous well-designed study indicated that splenectomy attenuated murine liver fibrosis[22].…”
Section: Discussionmentioning
confidence: 99%
“…Although splenectomy is performed for patients with hypersplenism in some institutions[21,42], hypersplenism in most patients should be considered a laboratory abnormality that does not require treatment or further consideration[43]. However, a previous well-designed study indicated that splenectomy attenuated murine liver fibrosis[22].…”
Section: Discussionmentioning
confidence: 99%
“…Advanced liver disease, such as cirrhosis, is often accompanied by hypersplenism and esophagogastric varices, which may contribute to esophageal and gastric variceal bleeding (EGVB) [ 15 , 16 ]. Furthermore, recent studies reported that splenectomy with periesophagogastric devascularization (SPD) is the optimal choice to manage hypersplenism and EGVB, with low incidence of complications and better liver function [ 17 24 ]. Additionally, SPD can contribute to decreased portal vein flow and increased hepatic artery flow via splenic arteriovenous disconnection [ 25 – 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the incidence of portal hypertension has also rapidly increased[ 24 ]. The majority of patients often present with liver dysfunction, bleeding, gastrointestinal vascular disease and other serious diseases, except common clinical symptoms, including hepatosplenomegaly and ascites[ 25 ].…”
Section: Discussionmentioning
confidence: 99%